PEDAGOGICAL CONDITIONS OF FORMATION OF ADAPTATION OF FOREIGN STUDENTS TO EDUCATIONAL ENVIRONMENT OF UNIVERSITIES OF UKRAINE - Hu, Zhunsi (Continuing Professional Education: Theory and Practice, 2019)
The article presents the pedagogical conditions of formation of adaptation of foreign students to the educational environment of Ukrainian universities. It described the essence of foreign students adapt to the educational environment of universities in Ukraine, which is a complex process of active adaptation and development of the personality of the applicant higher education of a foreign country to the educational space of another country. Identify and characterize the pedagogical conditions for successful adaptation of foreign students to the educational environment of universities in Ukraine as a set of established in the educational process of leading the circumstances to ensure the effectiveness of foreign youth adaptation to the cultural-educational environment of Ukrainian universities: the implementation of foreign students to adapt the program to the cultural and educational environment of the university, providing intercultural adaptation of all participants of the process, conducting the monitoring of adaptation. The content and structure of foreign students to adapt the program to the educational environment of universities in Ukraine, cross-cultural training. The purpose of the adaptation of the program: to ensure a gradual, systematic and scientifically sound mastery of foreign students the basic culture of the new educational environment and to carry out their acculturation in it. The basis of the program of adaptation of foreign students to the educational environment of universities in Ukraine imposed measures aimed at ensuring the socio-cultural, socio-psychological and didactic adaptation that define the essence of adaptation activities, the implementation of which it is possible to realize several goals.